PENGARUH KUDETA MILITER MYANMAR TERHADAP STABILITAS KAWASAN ASEAN PADA TAHUN 2021 - Fadhlan Nur Hakiem; Tania Amelinda Hasanah; Annisa Febrianti Putri Indrasari (Review of International Relations, 2022)
This study aims to find out how to get out of the problem of myanmar military coup, especially fellow member states in a region in terms of the presence or absence of upheaval from various aspects such as: social, economic, political, defense and security. The incident in February 2021 was recorded as the second coup that occurred in Myanmar. In responding to the political crisis that occurred in Myanmar, ASEAN seems to find it difficult to get out of the principle of non-interference, where the political crisis that occurred in one of the ASEAN countries became the internal affairs of the country concerned. ASEAN must be gentler to intervene and exert pressure through a heartfelt attitude such as the threat of removing Myanmar from ASEAN if the military leader is not willing to end the coup. This is a challenge for ASEAN, because stability in the ASEAN region will be further disrupted if the rejection of reconciliation cannot be carried out in the future. This research will apply the Regional Security Approach and the Human Security Approach which is considered appropriate to be applied to this research. The method used in writing this journal is descriptive qualitative with the data collection technique using the library research method. Research shows that the influence of Myanmar's military coup on the stability of the ASEAN Region is increasingly felt. ASEAN must learn how to apply the concept of non-intervention more flexibly to the Myanmar issue.